Population structure of Tagnanan Coconut (Cocos nucifera L.) and correlation among fruit yield and quality traits - Kingimi, Mohammed; Mohamad Zaki, Nurqistina Atiqah; Naharudin, Nazatul Shima; Sinniah, Uma Rani; Ahmad Hamdani, Muhammad Saiful; Sulaiman, Zulkefly (WMIT Group Sdn Bhd, 2023)
MATAG is one of Malaysia's widely cultivated coconut hybrids for its high fruit yield and quality traits, utilized in various food and nutraceutical products. It is obtained from the cross between Tagnanan, a tall-type coconut, with Malayan dwarf coconut varieties. The low success rate and inconsistencies in MATAG hybrid production were possibly due to the condition of Tagnanan as the pollen source, as tall-type coconuts are generally allogamous, making them heterogeneous. The study was conducted to obtain the phenotypic data on yield and fruit quality to describe the population structure and relationship among traits of the Tagnanan population at DOA, Teluk Bharu, Perak. One hundred palm of 12 years old were selected as representative of the whole Tagnanan population, where phenotypic and fruit quality data were collected. Generally, the Tagnanan population was divided into six clusters. Cluster 4, with 67 of the sample population, performed best in terms of meat weight and fruit yield. Cluster 3 grouped individuals with high shell weight and shell and copra thickness. Correlation analysis shows a strong positive relationship between fruit weight, nut weight, split nut weight and most fruit quality traits. However, a negative correlation existed between copra thickness and shell thickness. Clustering of individuals in the sample population of Tagnanan based on their phenotypic performance is an essential step in identifying and selecting groups with high fruit yield and quality. Understanding the relationship among fruit quality components enables the estimation of correlated responses in selecting these traits. Selection of these individuals based on their cluster allows the improvement of the Tagnanan population by only harvesting nuts from these clusters to form the new population as a pollen source for Matag hybrid production.